Enhancing Business Communication in the Hotel Industry through Artificial Intelligence: Evidence from Pokhara, Nepal - Timilsina, Angela; Lamichhane , Yog Raj (Journal of Development and Social Engineering, 2024)
Incorporating artificial intelligence (AI) in the hotel sector transforms business communication and boosts operational effectiveness. The qualitative study examines how AI enhances business communication between hotels and their guests, emphasizing immediate responses, tailored services, and operations management. AI technologies such as chatbots, automated messaging platforms, and predictive analytics facilitate customer interactions, improving guest experiences and business results. This study assesses the advantages of adopting AI, which include faster response times, customized marketing approaches, and enhanced business operations. It also recognizes obstacles, like technological constraints, significant implementation expenses, and employee reluctance towards utilizing AI. Within a qualitative approach, the primary data was gathered through semi-structured in-depth interviews with five hotel proprietors and managers selected for their roles in overseeing operations and implementing AI technologies for business communication. The results emphasize that, although AI improves efficiency and guest contentment, it is essential to find a balance between automation and human interaction to preserve the personal touch that is vital to hospitality. Furthermore, tackling infrastructure issues and offering staff training are key factors for the effective implementation of AI. Finally, the study concludes with suggestions for leveraging AI’s capabilities in the hospitality industry while ensuring ethical practices and respecting cultural sensitivities.